Limites e possibilidades formativas da webquest como atividade de pesquisa na formação docente em química - Araújo, Sandra Cristina Marquez (2010)
The present investigation objectified analyzes the limits and possibilities formatted of webquest to introduce the research on teaching formation on chemistry. For so, we started from the research choiced from Demo (1997; 2002) Maldaner (2000) and Galiazzi (2003) that pointed, between others characteristics of research job, the new elaboration of knowledge by the allowing that by himself assume how author of your formation, I mean, it´s capable of build knowledge from own initiating, learning how to learn. The investigation occur on discipline context of supervised curricular probation in chemistry IV from a licenciature in chemistry from Itumbiara GO. Opted for one investigation of qualitative kind, ruled on case studying, for develop on natural scene, reach on a descriptive scenery, reach on a descriptive data, focus on process and the variables that interfere on the research way. To catch and register the data were used the questionnaire, recording in audio and camp notes. The analyses shows that the elaboration of webquest become possible the development of capacities ah abilities needed to the research: the search and the new construction of the knowledge. But the academician present difficult to the decisions and dependence to models and standard to be followed. The result indicate the necessity of this abort during the initial formation of the teacher for the same become better your practice on research to your context and become a researcher. The webquest produced were changed, seen that some groups showed bigger interest and dedication, once that the work with the research need a give a bigger time to study and base. How consequence, the webquest sows the meaning potency on research teaching formation to become possible the use of informations available on building of knowledge from an emancipated form. Meanwhile we should detach that this is a process that once mobilized on initial formation, must be extend during all the existence and teacher practice with different formative strategy.